Does Trade and Technology Transmission Facilitate Inequality Convergence? : An Inquiry into the Role of Technology in Reducing the Poverty of Nations - Das, Gouranga Gopal (IMF Working Papers; Working Paper, 2007)
Based on stylized evidence showing variation of the Gini coefficient of income inequality across skill cohorts and on the rapid rise in trade in technology-intensive goods, the ripple effects of technology transmission and income inequality are explored in a global Computable General Equilibrium (CGE) framework. An exogenous technology shock transmitted via trade from the United States induces productivity growth in developing regions. This spillover capture-aided by absorptive capability, better governance and institutions, technological symmetry and social acceptance-causes income to increase and income inequality to decline. The conjoined parameters retard growth's inequality-enhancing effect and thus facilitate long-run convergence of inequality between nations.